International encyclopedia of civil society - List, Regina A.; Anheier, Helmut K.; Toepler, Stefan (Springer Nature Living Reference Social Sciences, 2019)
Intro -- Foreword -- Acknowledgments -- Encyclopedia Entries -- Conclusion -- Appendix -- Index